Immunoprotective effect of chitosan nanoparticles with different particle sizes against H9N2 avian influenza infection - Shangen Xu; Zhi Zhao; Chenxi Sun; Yile Ji; Qingshuang Luan; Qihong Zhang; Zheng Jin; Kai Zhao (Poultry Science)
H9N2 is the most common avian influenza virus (AIV), which causes significant losses in chickens. Safe and effective vaccines are crucial for the prevention of H9N2 AIVs. Chitosan nanoparticles, as novel adjuvants, enhance vaccine immunity and biocompatibility; however, the impact of particle size on the immunological effects remains underexplored. To solve these problems and to prepare an efficient novel H9N2 vaccine, we constructed four N-2-HACC/CMCS NPs (NHC NPs) of different particle sizes (165.6 ± 12.0 nm, 272.5 ± 7.0 nm, 343.2 ± 8.0 nm, and 443.5 ± 15.0 nm). Subsequent in vivo immunogenicity screening revealed that H9N2 with the 272.5 ± 7.0 nm NHC NPs vaccine group induced higher levels of neutralizing antibodies in the early stage of the immune response, while the 343.2 ± 8.0 nm NHC NPs vaccine group induced higher levels of neutralizing antibodies in the late stages of the immune response. Subsequently, the results of the optimal particle size combination screening revealed that more neutralizing antibodies were induced when the NHC NPs particle size combination of 272.5 ± 7.0 nm:343.2 ± 8.0 nm ratio was 1.5:1. This optimal particle size combination for NP vaccines promoted lymphocyte proliferation, induced higher IgG2a/IgG1 ratios, and promoted the production of cytokines (i.e., IL-2, IL-4, and IFN-γ). Moreover, a mechanistic analysis revealed that the optimal NHC NPs combination triggered the activation of antigen presenting cells via TLR4 and participated in immune responses through the production of NO and TNF-α. Taken together, our study revealed that the optimal combination of NHC NPs may be a promising strategy against influenza viruses.